Biological soil crust and disturbance controls on surface hydrology in a semi‐arid ecosystem. Issue 3 (10th March 2017) - Faist, Akasha M.; Herrick, Jeffrey E.; Belnap, Jayne; Van Zee, Justin W.; Barger, Nichole N.
Abstract: Biological soil crust communities (biocrusts) play an important role in surface hydrologic processes in dryland ecosystems and can be dramatically altered with soil surface disturbance. In this study, through a simulated rainfall experiment, we examined biocrust hydrologic responses to disturbance (trampling and scraping) at different developmental stages on sandy soils on the Colorado Plateau. Our results showed that all disturbance treatments of the early‐successional light cyanobacterial biocrusts reduced runoff after 10 min of cumulative rainfall. Scraped and scraped + trampled treatments also reduced runoff after 30 min in the light biocrust when compared to the intact controls but runoff in the trampling treatments was not significantly reduced. Light biocrust sediment loss trended toward a decrease in total amount of sediment lost in all disturbance treatments but not significantly so. In contrast, trampling well‐developed dark cyano‐lichen biocrusts demonstrated an opposite response than the less‐developed light biocrusts and increased runoff after 30 min of cumulative rainfall and in total sediment loss relative to intact controls. Scraping in dark crusts did not increase runoff, implying that soil aggregate structure was important to the infiltration process. Well‐developed, intact dark biocrusts generally had lower runoff and sediment loss and highest aggregate stability, whereas the less‐developed light biocrusts were highest in runoff and sediment loss after disturbance when compared to the controls. These results suggest the importance of maintaining the well‐developed dark biocrusts, as they are beneficial for lowering runoff and reducing soil loss and redistribution on the landscape. These data also suggest that upslope patches of light biocrust may either support water transport to downslope vegetation patches or alternatively this runoff may place dark biocrust patches at risk of disruption and loss, given that light patches increase runoff and thus soil erosion potential.